New Enclosure of the Commons: A Human Rights Critique of Rights to Cultivate in the Capital City of Nusantara - Iswantoro (UIN Sunan Kalijaga Yogyakarta, 2025)
Rights to Cultivate in the Capital City of Nusantara (IKN), which allows control for up to 190 years, reflects a shift in resource governance in Indonesia from a social paradigm toward an economic orientation centered on capital accumulation. This shift reveals that agrarian law is no longer an instrument of social justice, but rather a means of legitimizing long-term control by capital. This research aims to interpret Rights to Cultivate in the IKN Law as a form of new enclosure of the commons, by tracing the changes in resource governance patterns that are institutionalized through state policy. Using a descriptive qualitative method based on regulatory studies and academic literature, the analysis finds that the Rights to Cultivate eflects practices of accumulation by Dispossession, double movement, and territorialisation by regulation, while at the same time contradicting the spirit of human rights in land management through the 1960 Basic Agrarian Law (UUPA), Article 33 of the 1945 Constitution, and commitments to economic, social, and cultural rights. This policy demonstrates a shift in resource governance toward a system that prioritizes capital and investment, yet overlooks the dimension of social justice. The Rights to Cultivate in the IKN Law can be interpreted as a new enclosure of the commons. This concept represents a new legal boundary that restricts people's access to their living space in the name of an institutionalized logic of capital. Kebijakan Hak Guna Usaha dalam Undang-Undang Ibu Kota Nusantara (IKN) yang memungkinkan penguasaan hingga 190 tahun mencerminkan pergeseran tata kelola sumber daya di Indonesia dari paradigma sosial menuju orientasi ekonomi yang berpusat pada akumulasi kapital. Pergeseran ini menunjukkan bagaimana hukum pertanahan tidak lagi menjadi instrumen keadilan sosial, tetapi sarana legalisasi penguasaan jangka panjang oleh modal. Penelitian ini bertujuan untuk memaknai HGU IKN sebagai bentuk new enclosure of the commons, dengan menelusuri perubahan pola tata kelola sumber daya yang dilembagakan melalui kebijakan negara. Menggunakan metode kualitatif deskriptif berbasis studi peraturan dan literatur akademik, analisis menemukan bahwa HGU IKN mencerminkan praktik accumulation by dispossession, double movement, dan territorialisation by regulation, sekaligus bertentangan dengan semangat hak asasi manusia dalam pengelolaan lahan melalui UUPA 1960, Pasal 33 UUD 1945, serta komitmen terhadap hak ekonomi, sosial, dan budaya. Kebijakan ini memperlihatkan transformasi tata kelola sumber daya menjadi sistem yang mengutamakan modal dan investasi, namun mengabaikan dimensi keadilan sosial. HGU IKN dapat dimaknai sebagai new enclosure of the commons. Konsep ini merupakan suatu pagar hukum baru yang menutup akses rakyat atas ruang hidupnya demi logika kapital yang dilembagakan.